ПРИНЦИПИ ПЕДАГОГІЧНОЇ СИСТЕМИ МАЙСТРА РЕАЛІСТИЧНОГО ЖИВОПИСУ Й ГРАФІКИ, ХУДОЖНИКА-БАТАЛІСТА - М.С.САМОКИША (Педагогіка вищої та середньої школи, 2009)
"Principles of the pedagogical system of master of the realistic painting and graphic arts. artist-painter of battlepieces - N.S. Samokisha" is examined question about the features of artistic-pedagogical activity of the known Ukrainian artist of large and scalene talent Mickolaja Se- menovicha Samokisha, individually his innovative elucidative measures and methods on teaching of artists- painters of battlepieces.